Design of Creative Learning Plans in Social Studies Using Infographics Technique to Develop Technology Competency of Primary Students, Tungfangwittaya School,Lampang Province - ละคำปา สวัสดิ์; มั่งคั่ง ชรินทร์; มณีกุล จารุณี (Community and Social Development Journal, 2019)
The objectives of this study were to 1) design of learning plans using Info graphic technic to develop the competency of using technology creatively of primary students, Thungfangwittaya School, Lampang Province 2) find the quality of learning plans and the assessment of competency of using technology creatively of primary students, Thungfangwittaya School, Lampang Province 3) create the evaluated tools for competency in using technology creatively and learning plans using Infographics Technic of primary students, Thungfangwittaya School, Lampang Province. The assessor consisted of 5 primary teachers, 2 secondary teachers both of them teaching social studies and 2 teachers who teach in technologyby purposive sampling of assessor total 9 experts. The study tools were the assessments with 5 levels The results of this study revealed that : the designing of learning plans using Info graphic technic to develop the competency of using technology creatively of primary students, Thungfangwittaya School, Lampang Province by using unit of Lampang khelangnakorn and doing activity in lesson plan with Info graphic technic via 9 experts for evaluation them. The designing of learning plans are complete and correct and the most appropriate quality for using the learning plans creatively in social studies as a point statistic the mean of 4.82 While the value of standard deviation is at 0.31 The creation of the evaluated tools for competency in using technology creatively of primary students, Thungfangwittaya School, Lampang Province by creating the criteria of the assessment of competency for primary students in using technology according to The core curriculum 2551 to be the guideline to create the assessment via 9 experts for evaluation them. The assessment of the competency in using technology creatively is creatively is the most appropriate quality for evaluation as a point statistic mean of 4.79 While the value of standard deviation is at 0.31 This study helps the teachers having the tools in teaching and enhance the knowledge and understanding for the students in their own locality and moreover, the students have the skill in using technology to develop the competence in using technology for themselves and social.